Visual homing for a mobile robot using direction votes from flow vectors - Stewart, R. L.; Mills, M.; Hong Zhang (2012 IEEE International Conference on Multisensor Fusion and Integration for Intelligent Systems, 2012)
This paper investigates the problem of robot visual homing - the navigation to a goal location by a mobile robot using visual sensory input. The visual homing approach taken is to consider the flow vectors between a robot's current view and a desired milestone view. The flow vectors can be used to determine an angular velocity command that attempts to align the two views under a constant forward speed. Experiments with a mobile robot have been conducted following the teach-replay approach. By using a sequence of milestone images taken successively along a path, preliminary results show that a robot can successfully repeat the path and navigate to its goal autonomously. The method should be useful for route following and other applications involving visual navigation.